Antimicrobial Photodynamic Therapy in the Post-Operative Extraction of Lower Third Molars: A Randomized and Blinded Clinical Trial (Revista da Faculdade de Odontologia - UPF, 2025)
Objective: This study aimed to evaluate local antimicrobial reduction protocols in post operative inflammatory-infectious events of lower third molar extractions. Methods It was a clinical, crossover, randomized and blind study with a sample of 22 patients (36 teeth). The patients underwent two surgical moments at intervals. The allocation of teeth was in 3 experimental groups: Group 1: Antimicrobial photodynamic therapy (aPDT); Group 2: 0.12% Chlorhexidine (CLX); Group 3: Control - 0.9% Saline Solution (SS 0.9%). The groups received treatment immediately after tooth extraction, and the evaluated parameters were: pain, edema, maximum mouth opening, and infection. Results: The data showed a statistically significant difference with aPDT therapy in edema, intragroup evaluation, and the distance between the gonial-tragus points (p = 0.022). In measuring mouth opening, there was a statistical difference in the intragroup assessment of aPDT and CLX (aPDT with p = 0.035, CLX with p = 0.038). There was a statistical difference in the presence of postoperative infection, with the aPDT and CLX groups showing the lowest values (p = 0.039). Regarding the pain, there was a decrease in the analysis on the 7th day of the aPDT group (P = 0.007). Conclusion: In conclusion, treatment with aPDT favors a statistically significant reduction of infection, edema, pain, and trismus in the postoperative period of third molar extractions.